Students Self-Directed Learning Using Blended Learning On Reading Subject In Higher Education - Aurellia, Stevenika Gabriela; Yulmiati, Yulmiati; Putri, Dian Mega (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Abstract. This study aimed to measure self-directed learning using blended learning in the reading subject in higher education. The researcher employed the descriptive method with a quantitative approach. Self-directed learning was the sole focus of the investigation. In line with Williamson, S. N., five aspects were to measured self-directed learning: awareness, learning strategies, learning activities, evaluation, and interpersonal skills. The researcher acquired data on self-directed learning through a questionnaire. The study's population comprised English students at Universitas PGRI Sumatera Barat during the 2022 academic year, totaling 55 students. Employing purposive sampling, the entire population of 55 students was included in the sample. Upon analyzing the collected data using SPSS 22, the researchers employed the percentage formula to ascertain the students' score distribution. The findings indicated a noteworthy 76% overall score, signifying a high level of self-directed learning. These outcomes suggest that students at Universitas PGRI Sumatra Barat exhibited robust traits of responsibility, persistence, self-control, discipline, and effective learning strategies.